Effects of fenugreek seed extract supplementation on growth performance, nutrient digestibility, diarrhoea scores, blood profiles, faecal microflora and faecal noxious gas emission in weanling piglets. Issue 6 (6th March 2016) - Begum, M.; Hossain, M. M.; Kim, I. H.
Summary: This study was conducted to evaluate the effect of dietary fenugreek seed extract (FSE) on growth performance, apparent total tract digestibility (ATTD), diarrhoea scores, blood profiles, faecal microflora and faecal gas emission in weanling pigs. A total of 135 weanling pigs [(Yorkshire × Landrace) × Duroc] with an average BW of (7.96 ± 1.03 kg; 28 days of age) were used in a 42‐day study. Piglets were randomly allotted to three experimental diets with nine replicate pens and five pigs per pen. Dietary treatments were as follows: CON, basal diet; FSE1, basal diet + 0.1% FSE; FSE2, basal diet + 0.2% FSE. Pigs were fed with phase 1 (0–14 days) and phase 2 (14–42 days) diets in the form of mash. Average daily gain (ADG) was linearly increased (p = 0.031) by FSE supplementation compared with CON diet during days 0–14. From days 14–42, FSE2 diet had increased ADG and growth efficiency (G/F) compared with the CON diet (p = 0.014 and 0.026 respectively). Moreover, ADG and G/F were increased by FSE supplementation during days 0–42 (linear, p = 0.037 and 0.014 respectively). Energy digestibility was higher (linear, p = 0.030) by FSE supplementation at 6 weeks. On day 42, dietary supplementation of FSE linearly increased red blood cells (RBC) and immunoglobulin G (IgG) concentration (p = 0.042 and 0.038 respectively). Piglets fed FSE2 diet had higher (linear, p = 0.025) serum high‐density lipoprotein cholesterol (HDL‐C) concentration compared with those fed CON diet. However, piglets fed FSE2 diet had linearly reduced faecal ammonia (NH3 ) and hydrogen sulphide (H2 S) gas emission compared with those fed the CON diet (p = 0.018 and 0.010 respectively). In conclusion, FSE supplementation increased the performance and reduced faecal gas emission in weanling pigs.